Understanding the impact of rural in-migrants on locals’ architectural tastes: Cultural assimilation or identity reinforcement. - Na Zhang; Ni Yan; Han, Song; Canxu Zeng; Yi Zhou; Zhengxu Zhou (Journal of Rural Studies, 2026)
Rural in-migrants often introduce distinctive architectural aesthetics, driving gentrification processes in rural areas. While this new aesthetic influences local residents' architectural preferences, the factors related to these preferences remain unclear. This study investigates how interactions with rural in-migrants are associated with locals' architectural tastes and identifies other socio-cultural factors. We developed an innovative two-dimensional matrix framework for assessing architectural preferences in rural in-migration contexts, integrating rural in-migration theory with acculturation theory and validated through phototesting techniques. Through a theory-building case study, we focused on 3 villages in Dali, China, which share similar cultural backgrounds but exhibit different architectural changes in response to rural in-migration. We surveyed 335 locals and 218 migrants across these villages in 2021. The results show that increased social interactions between locals and migrants are significantly associated with strengthened local preferences for locality-based architectural styles over globalized ones, accompanied by a narrowing of the aesthetic distance between the two groups. These findings suggest that cultural interaction processes may reinforce rather than replace local aesthetic preferences. However, this effect varies among locals due to differences in community characteristics, urban experience, future residential intentions, age, education, and marital status. This study shows that local residents demonstrate agency in cultural adaptation rather than remain passive recipients, suggesting potential pathways for communities to resist marginalization in the gentrification process.